2006
DOI: 10.1016/j.trstmh.2005.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic particles in the skin of inhabitants of volcanic areas of Central America: their possible immunomodulatory influence in leishmaniasis and leprosy

Abstract: We have evaluated biopsies from patients with atypical nodular and typical ulcerated lesions of cutaneous leishmaniasis, from leishmanin reactions and skin from normal individuals from Nicaragua, Honduras and Guatemala for the presence of inorganic particles using confocal microscopy with a polarised light source and conventional histopathological techniques. Analysis by semiquantitative confocal microscopy permitted the demonstration of significantly larger numbers of particles in atypical lesions. Silica and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In Ecuador the disease is known as angry sore (“sarna brava”), Colombian ulcer, or mountain leprosy (mucocutaneous leishmaniasis) . Interestingly, in some countries of Central America where the disease appears to be modulated by the presence of inorganic particles contained in volcanic emanations, the disease is also known under the term of “mountain leprosy.”…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ecuador the disease is known as angry sore (“sarna brava”), Colombian ulcer, or mountain leprosy (mucocutaneous leishmaniasis) . Interestingly, in some countries of Central America where the disease appears to be modulated by the presence of inorganic particles contained in volcanic emanations, the disease is also known under the term of “mountain leprosy.”…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Interestingly, in some countries of Central America where the disease appears to be modulated by the presence of inorganic particles contained in volcanic emanations, the disease is also known under the term of "mountain leprosy." 11,12 Cutaneous leishmaniasis is usually classified under two headings: Old World, which comprises geographically southern Europe, the Middle East, Asia, and Africa, and New World cutaneous leishmaniasis, embracing Latin America. However, while most of the Old World species cause benign cutaneous disease, New World species cause a spectrum of disease ranging from mild cutaneous forms to also include severe mucosal lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the Icelandic eruption, Carlsen et al (2012) reported that Icelanders exposed to Eyjafjallajökull volcanic ash had increased prevalence of respiratory symptoms, specifically asthma and chronic bronchitis, compared with a control population in northern Iceland. Although other studies have shown that exposure to volcanic ash increases the risk of developing respiratory infections (Convit et al 2006; Gudmundsson 2011; Naumova et al 2007), there are limited data on the cellular mechanisms involved in this increased lung infection risk. Because airway infections are the result of impaired innate immune mechanisms, we hypothesized that volcanic ash impairs innate immune mechanisms, specifically the function of macrophages and antimicrobial peptides.…”
mentioning
confidence: 99%
“…In human hosts in Central America, Convit et al (2006) observed an interesting phenomenon linked to a frequent atypical form of cutaneous leishmaniasis (AtypCL) in patients. This atypical benign form is characterized by nonulcerating nodules containing a few parasites (L. chagasi, L. mexicana).…”
Section: Leishmania Spp and Environmentmentioning
confidence: 99%